2001
DOI: 10.1099/00221287-147-1-121
|View full text |Cite
|
Sign up to set email alerts
|

The chlorobenzoate dioxygenase genes of Burkholderia sp. strain NK8 involved in the catabolism of chlorobenzoates

Abstract: Burkholderia sp. NK8 grows abundantly on 3-chlorobenzoate (3CB), 4-chlorobenzoate (4CB) and benzoate. The genes encoding the oxidation of (chloro)benzoates (cbeABCD) and catechol (catA, catBC), the LysR-type regulatory gene cbeR and the gene cbeE with unknown function, all of which form a single cluster in NK8, were cloned and analysed. The protein sequence of chlorobenzoate 1,2-dioxygenase (CbeABC) is 50-65 % identical to the benzoate dioxygenase (BenABC) of Acinetobacter sp. ADP1, toluate dioxygenase (XylXYZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 45 publications
2
46
0
Order By: Relevance
“…For example, CbeR (11) and CbnR (12) of Burkholderia sp. NK8 and Ralstonia eutropha NH9, respectively, respond to muconate, benzoate, and͞or chloro-substituted versions of these compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, CbeR (11) and CbnR (12) of Burkholderia sp. NK8 and Ralstonia eutropha NH9, respectively, respond to muconate, benzoate, and͞or chloro-substituted versions of these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Although multiple effectors sometimes regulate gene expression (11)(12)(13)(14)(15)(16)(17), the combined effect of these compounds on transcriptional control by a single regulator is poorly understood. Synergistic effects on transcriptional regulation have previously been attributed to two distinct contacts made between RNA polymerase and a single DNA-bound activator or between RNA polymerase and two different activators, as reviewed in ref.…”
mentioning
confidence: 99%
“…To date, various bacteria that can degrade CBs have been isolated from different environmental samples 3,[6][7][8]15,25,29) . It is not clear, however, which bacterial groups are the main contributors to the degradation of CBs under environmental conditions, because most of the degraders are obtained by screening based on their ability to degrade CBs on agar plates or in liquid cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Although 3CB-degrading Burkholderia spp. have been isolated from various soils 12,14,15,32) , it had not been confirmed whether this group of bacteria contributes to the degradation of 3CB in the soil environment. Our results suggest that several Burkholderia strains actually function as effective 3CB-degraders in soil.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorobenzoates can be generated from the biodegradation of polychlorinated biphenyls 11) , and 3CB has been most frequently used to study the bacterial degradation of this group of compounds. Up to now, 3CB-degrading bacteria have been isolated from environmental samples based on their 3CB-degrading ability in culture media 4,6,[12][13][14][15][16]20,29,31) , but there have been few attempts to isolate these degraders based on their ability in the environment. Previously, we showed that several Burkholderia-like bacteria became dominant in a forest soil after 3CB was added, by PCR-DGGE targeting the 16S rRNA gene and benzoate 1,2-dioxygenase alpha subunit gene (benA) 25) .…”
mentioning
confidence: 99%